Why People Vote: Estimating the Social Returns to Voting. Issue 2 (20th October 2014) - Gerber, Alan S.; Huber, Gregory A.; Doherty, David; Dowling, Conor M.
Abstract : This article measures the social rewards and sanctions associated with voting. A series of survey experiments shows that information about whether a person votes directly affects how favorably that person is viewed. Importantly, the study also compares the rewards and sanctions associated with voting to other activities, including the decisions to recycle, volunteer and return one's library books on time. It presents a behavioral test of the consequences of non-voting and finds that individuals are willing to take costly action in a dictator game to reward political participation. Finally, it shows that survey measures of social norms about voting are correlated with county-level voter turnout. The study adds to the growing literature documenting the important influence of social concerns on turnout and other political choices.